An Evaluation of Stauffenberg's Actions in the Film Valkyrie (2008) from the Perspective of the Virtue of Altruism - Hamidullah Genç (Marifetname, 2023)
Cinema is an effective means of cultural representation as it reaches all corners of the world through its narrative styles and products. Cinema portrays external realities and mental experiences in artistic, documentary, and dramatic forms, depicting various subjects with different themes. Therefore, every film in the information- flow medium of cinema has a conceptual and philosophical background. The film Valkyrie (2008), set during a period of war, depicts a character's efforts to alleviate pain by prioritizing others and endangering himself and his loved ones in the process. These efforts demonstrate his motivation for altruism. Cinema has benefited us by identifying, capturing, and examining altruism in a simulative sense. This study aims to reveal the contrast of altruism with "self-centeredness" and "egoism," which are seen as virtues by different philosophical thinkers, by discussing the characters in the film, especially Stauffenberg’s stance on these virtues. The theoretical framework regarding these concepts has been created in the first subheading, and in the second subheading, the position of the character(s) compared to Stauffenberg has been determined within this framework. The first subheading entails a semantic analysis of altruism from the perspective of different thinkers, summarizing the difference between the concept and "egoism" and "self-centeredness." The second subheading includes a framework related to the fictional dimension of the film reviewing critical articles on "Valkyrie." Stauffenberg's struggle against Nazis during World War II has been examined considering apparent virtue. Using the qualitative content analysis method, the film has been analyzed, and Stauffenberg's altruistic stance is interpreted based on philosophical and moral data. The conclusion is that Stauffenberg acted in accordance with altruism, not with self-centeredness or egoism.